Design and analysis of a new down‐the‐hole electromagnetic hammer driven by tube linear motor. Issue 9 (25th July 2017) - Wu, Tao; Tang, Yiru; Tang, Shengwen; Li, Yongbo; He, Wangyong; Chen, E
Abstract : Percussive‐rotary drilling is an effective method for the hard rock drilling. As hydraulic and pneumatic hammers have many problems especially in the deep core drilling, a new electromagnetic hammer driven by a tube linear motor is introduced in this study. The study mainly covers the mechanical structure and electromagnetic design of the hammer, respectively. Due to the direct use of electric power, the electromagnetic hammer has the advantage of high efficiency while it must meet the minimal percussive energy requirement under the limitation of drill pipe diameter. In this study, the validity of electromagnetic design is verified through the finite‐element analysis software Ansoft/Maxwell 2D and numerical calculation of electromagnetic force. The working temperature in deep down‐hole is relatively high, the influence of high temperature in deep hole on the electromagnetic thrust of the linear motor is then analysed. A motion model of linear motor hammer is established to calculate and analyse the impact power and frequency under different conditions. The results show that the performance of linear motor hammer can reach or even exceed the one of same diameter hydraulic hammer, especially in the low‐frequency range. The prototype test also confirms the validity of the design.